(untitled) - Chapman, Audrey R. (Washington, D.C., 2000)
The combined contributions of science and religion to resolving environmental problems are far greater than each could offer working in isolation. Scientific findings are central to understanding the impact of human populations on the environment, but a more ecologically sustainable future will require radical changes in values, lifestyle choices, and consumption patterns-a revolution that falls squarely within the domain of the religious community. Consumption, Population, and Sustainability is an outgrowth of a conference sponsored jointly by the Boston Theological Institute and the American Association for the Advancement of Science that brought together more than 250 scientists and people of religious faith to discuss the environmental impact of consumption patterns and population trends, and to consider alternative and more equitable value systems, economic arrangements, and technologies that will be necessary for achieving a more sustainable future.
Keywords: Consumption (economics),Consumption (economics),Population policy,Population policy,Sustainable development; Religious aspects,Moral and ethical aspects,Religious aspects,Moral and ethical aspects,Moral and ethical aspects